Exploring a Research Method - Interview - Wang, Shiyun (Advances in Social Sciences Research Journal, 2015)
There are many research methods exist in the educational research. For example, the interviews, the observations, the surveys, the action research, and so on. As a researcher, he/she can select these methods in the process of the research. In this essay, I focus on one of the educational research data generation methods--- the interview. I will analyze and discuss the interview in detail. First of all, I will comment on the question “what is the interview’’. The definition of the interview will be described from different aspects and situations, some definitions the former researchers give us will be introduced. At the same time, my understanding about the definition of the interview will be added in this section. Secondly, the main characteristics of the interview will be discussed. The quality of the interview will be explored. Thirdly, I will analyze some key factors of the interview. Fourthly, the ethical implication will be considered.